2014
DOI: 10.1186/2197-4284-1-16
|View full text |Cite
|
Sign up to set email alerts
|

Observations of GPS scintillation during an isolated auroral substorm

Abstract: This paper reports simultaneous observations of ionospheric scintillation during an auroral substorm that were made using an all-sky full-color digital single-lens reflex (DSLR) camera (ASC) and a Global Positioning System (GPS) ionospheric scintillation and total electron content monitor (GISTM) in Tromsø (69.60 N, 19.20 E), Norway. On the night of November 19, 2009, a small substorm occurred in northern Scandinavia. The ASC captured its temporal evolution from the beginning of the growth phase to the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
(31 reference statements)
2
32
0
Order By: Relevance
“…Hosokawa et al (2014) also suggested that strong phase scintillation in the nighttime auroral oval is mostly due to the large scale ionospheric irregularity generated due to the structured precipitation of particles on the scale of a few tens of meters to a few tens of kilometers. On the other hand Figures 3F,H confirms that the BBAE auroral emission is in the vicinity of strong phase scintillation, therefore, the BBAE is mostly due to the large scale ionospheric irregularity generated due to the energetic particle precipitation due to substorm, on the scale of few tens of meters to few tens of kilometers (Hosokawa et al, 2014).…”
Section: Bouncing Boundary Auroral Emissions (Bbae)mentioning
confidence: 99%
See 4 more Smart Citations
“…Hosokawa et al (2014) also suggested that strong phase scintillation in the nighttime auroral oval is mostly due to the large scale ionospheric irregularity generated due to the structured precipitation of particles on the scale of a few tens of meters to a few tens of kilometers. On the other hand Figures 3F,H confirms that the BBAE auroral emission is in the vicinity of strong phase scintillation, therefore, the BBAE is mostly due to the large scale ionospheric irregularity generated due to the energetic particle precipitation due to substorm, on the scale of few tens of meters to few tens of kilometers (Hosokawa et al, 2014).…”
Section: Bouncing Boundary Auroral Emissions (Bbae)mentioning
confidence: 99%
“…The scintillation observations shown in Figures 1, 2 also confirm the ionospheric scintillation occurring at the different MLATs beyond the red line boundaries of the FBAE and BBAE. Based on the previous polar ionospheric scintillation studies (e.g., Hosokawa et al, 2014;Jin et al, 2014;van der Meeren et al, 2014van der Meeren et al, , 2015 and the references therein) we can say that the strong phase scintillations with almost weak amplitude scintillation shown in Figures 2C,D above the upper boundary of the BBAE maybe associated to the fast moving polar cap patches, which are beyond the field of view of the ASI deployed at the CYRS. The weak amplitude as well as weak phase scintillations, above the upper auroral emission boundary during the FBAE might have occurred mostly due to the background ionosphere.…”
Section: Bouncing Boundary Auroral Emissions (Bbae)mentioning
confidence: 99%
See 3 more Smart Citations